ANALISIS PERENCANAAN PENGEMBANGAN PERPUSTAKAAN DIGITAL DI SMA NEGERI 1 CIMALAKA - Haria Saputry Wahyuni; Diah Sri Rejeki; Merryam Agustine (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Limited library space to support the availability of collections and also service time is sometimes an obstacle in the process of developing a library that is desired by students with increasingly diverse information needs in meeting learning information needs. In order to support online school activities in the future, like it or not, schools need to develop libraries in a digital direction so that all collections which are student learning resources can be accessed anywhere at any time without being limited by distance and time which have been obstacles. This is done so that students can make maximum use of all the learning resources provided according to their needs. This research aims to determine the development of the digital library at SMA Negeri 1 Cimalaka. The method used in this research is descriptive qualitative by triangulating the data. The result of this research is that the new library has a library automation application, in other words there is no digital library or school website available so that access to learning resources and utilization of collections cannot be utilized optimally by all students, teachers and also education staff at SMAN 1 Cimalaka. It is hoped that the development of the digital library at SMAN 1 Cimalaka can increase the maximum use of library facilities and learning resources without being limited by space, distance and time and can make library management more efficient and more modern